Effectiveness of fly traps with a variety of baits on the number of flies trapped in the primary market among farmers in Batu city - Hasbi Ash Shiddiqy; Muhammad Al-Irsyad; Agung Kurniawan; Hartati Eko Wardani (CV Rezki Media, 2025)
Background: Diarrhea is one of the top ten diseases in Batu City. One of the vectors causing this disease is flies, often found in traditional market environments. Fly control efforts can be carried out using traps combined with various types of bait, but the effectiveness of trap and bait variations has not been systematically studied. Objectives: This study aims to determine the effectiveness of fly traps with various baits on the number of flies trapped in Among Tani Main Market, Batu City. Methods: This study used a quasi-experimental design with a posttest-only group design. The variables observed were the number of flies trapped in three types of traps (bottles, nets, and blocks) and three variations of bait (shrimp, fish gills, and chicken offal). Traps were set for two hours for three days with three repetitions. The instruments used were modified fly traps and laboratory inventory. Data were analyzed using Levene's test for homogeneity and one-way ANOVA to determine differences between treatments. Results: ANOVA test results showed no significant difference (p > 0.05) between bait and trap variations in the number of flies trapped. However, bottle traps with fish gill bait descriptively showed the highest number of catches (395 flies over three days). Conclusions: Although there was no statistically significant difference, the bottle trap with fish gill bait was descriptively the most effective at catching flies. This study suggests using bottle traps with fish gill bait as an alternative to fly control in the market environment. Further research is recommended to examine the effect of environmental conditions and types of fly species on the effectiveness of traps and baits.